2022
DOI: 10.1155/2022/7781910
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits High Glucose-Induced H9c2 Cardiomyocyte Hypertrophy and Damage via RAGE-Dependent Inhibition of the NF-κB and TGF-β1/Smad3 Pathways

Abstract: Hyperglycaemia is associated with the development of cardiac vascular disease. Resveratrol (RES) is a naturally occurring polyphenolic compound that possesses many biological properties, including anti-inflammatory properties and antioxidation functions. Our study aimed to explore the RES’s protective roles on high glucose (HG)-induced H9c2 cells and the underlying mechanisms. Small-molecule inhibitors, western blotting (WB), as well as reverse-transcription PCR (RT-PCR) were employed to investigate the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Resveratrol is a polyphenolic compound widely discovered in a variety of medicinal and edible plants, with anti-inflammatory, antioxidant, and anti-apoptotic pharmacological effects (Gambini et al, 2015). Zhu et al (2022) found that TGF-β1, a-SMA, ColI, and Smad3 were significantly expressed in HG-induced H9c2 cells and were downregulated by resveratrol treatment. Such findings reveal that resveratrol reduces the ECM deposition by restraining the activation of TGF-β1/Smad3 signaling pathway, thereby alleviating the HGinduced cardiac fibrosis.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Resveratrol is a polyphenolic compound widely discovered in a variety of medicinal and edible plants, with anti-inflammatory, antioxidant, and anti-apoptotic pharmacological effects (Gambini et al, 2015). Zhu et al (2022) found that TGF-β1, a-SMA, ColI, and Smad3 were significantly expressed in HG-induced H9c2 cells and were downregulated by resveratrol treatment. Such findings reveal that resveratrol reduces the ECM deposition by restraining the activation of TGF-β1/Smad3 signaling pathway, thereby alleviating the HGinduced cardiac fibrosis.…”
Section: Polyphenolsmentioning
confidence: 99%
“…In patients with diabetes, a large number of AGEs are formed and deposited in the myocardial microvascular endothelium and extracellular matrix by non-enzymatic glycation reaction under long-term continuous high glucose environment [ 63 ]. AGEs can change the structure of proteins, cross-link collagen molecules, and directly cause irreversible damage to myocardial microvascular endothelial cells [ 64 , 65 ]. In addition, AGEs bind to RAGE and activate AGE-RAGE signaling pathways, causing oxidative stress, inflammatory response, and protein kinase C activation, which further promote ROS production [ 66 , 67 ].…”
Section: Oxidative Stress Signaling Pathways In Dcmmentioning
confidence: 99%